Konsep Dasar Ilmu Agama Islam Antara Keimanan dan Kehidupan - Zefanya Simalango; Joel Fernandes Gultom; Noak Yasai; Chalvin Christian Sihite; Liyus Waruwu (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Islam is one of the largest religions in Indonesia. Almost half of Indonesia's population adheres to Islam. Islam has an important and strategic role in shaping the morals and personality of its adherents. This can be interpreted as an effort to increase faith, understanding, appreciation, and practice of Islamic values, so as to give birth to Muslim individuals who have faith, piety, and noble character. Thus, Islamic teachings become a guide in personal life, society, nation, and state. This research aims to find out the history and basic teachings of Islam and the concept of Islamic teachings, so that we can understand the basics of teaching Islam. This research is expected to produce a more comprehensive understanding of Islamic teaching as the basis for the formation of the character and identity of Muslims in Indonesia.